Selection of Best-Suited Wind Turbines for New Wind Farm Sites Using Techno-Economic and GIS Analysis in South Korea - Sajid Ali; Choon-Man Jang (Energies, 2019)
South Korea greatly depends upon foreign countries to fulfill its energy requirements, and therefore imports billions of barrels of oil every year. For instance, 94.8% of the total primary energy supply (TPES) was imported from other countries in 2015, at the cost of 91.51 billion euros. There is a realistic challenge in front of the government to reduce these oil imports, and to find alternate (local) sources of energy. Renewable energy (RE) technologies can play a vital role in this regard. The South Korean government has shown a great interest in RE, and intends to achieve a target of 11% of the TPES being generated by RE by the end of 2035, as decided in the Korean Renewable Portfolio Standard (RPS); which showed that only 4.9% of TPES was produced by RE at the end of 2015. The present study proposes ten potential onshore wind farm sites. These locations have been identified by using the GIS−MCDM (geographic information system−multi-criteria decision-making) methodology and a detailed techno-economic assessment has also been presented. Furthermore, the appropriate type of wind turbines has been recommended for each site using detailed analysis of wind conditions, 50-year extreme wind speed (EWS) and turbulence intensity (TI). The analysis showed that all the sites have excellent wind conditions, and they are also economically feasible. Parameters such as AEP (annual energy production), CF (capacity factor), LCOE (levelized cost of electricity), and NPV (net present value) have been estimated for each site, using five different wind turbines manufactured in South Korea. The present study can be very useful for the wind energy sector in South Korea.